Library Human Resources Training Through Online-Based Service Provider Platform - Ashary, Muhammad Islah Addaulah; Komara, Diemas Arya (Edulib, 2022)
Almost all aspects of  life, the need for diverse human resources in modern times makes institutions and  human resources, in this case, human resources, design and carry out HR training  to improve library capabilities so that they can provide the best service to their  students' user. The purpose of this study is to find out how library HR training can  be carried out by utilizing online-based service provider platforms, as we know  that with a variety of new capabilities and technological developments, creating a  remote training system that is efficient and easily accessible by anyone. The  research method is a qualitative approach and literature study using related  literature in library studies by finding scientific literature. The results of the study  indicate that the use of LMS and online training platforms is a positive thing to be  used as a choice for HR training of an institution with the selection of training  tailored to the needs and desires of the HR who will participate.